Mechanisms and Management of Senescence - Heshmati, Hassan M. (Physiology, 2022)
Senescence represents a complex universal phenomenon that can be impacted by several factors. It is emerging as a therapeutic target for several diseases. This book presents an overview of the current mechanisms and management of senescence in humans. It also provides comparative data on senescence in animals and plants.